BIBLIOGRAPHY ON THE SOCIOLOGY OF CHILDHOOD: SELECTIVE AND PARTIALLY ANNOTATED - Thorne, Barrie (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
READINGS, FILMS, AND OTHER RESOURCESBIBLIOGRAPHY ON THE SOCIOLOGY OF CHILDHOOD: SELECTIVE AND PARTIALLY ANNOTATED